Pandemic-Related Stress Symptoms Among Norwegian Parents of Adolescents in Grades 6 to 8 - Idsoe, Thormod; Dyregrov, Atle; Janson, Harald; Nærde, Ane (Frontiers in Psychiatry, 2021)
We investigated pandemic-related stress symptoms during the first COVID-19 lockdown period in spring 2020 among parents of children that were 12 to 14 years old in the study period. Altogether 147 couples reported about their own trauma-related stress symptoms following the outbreak of the pandemic. Among the respondents, 9.5% of the mothers and 10.2% of the fathers had scores over cutoff on the screener (IES-6) measuring stress symptoms, but this was not a significant gender difference. Scores on the screener were not associated with family contamination or lockdown consequences. Family activities during lockdown did not moderate the impact of the pandemic on stress symptom levels. Whereas the experience of the COVID-19 pandemic will pose a stressor to most people, it is unlikely to be a criterion A event for many.